Enhanced susceptibility to cortical spreading depression in two types of Na+, K+-ATPase α2 subunit-deficient mice as a model of familial hemiplegic migraine 2. (August 2018) - Unekawa, Miyuki; Ikeda, Keiko; Tomita, Yutaka; Kawakami, Kiyoshi; Suzuki, Norihiro
Background: Patients with familial hemiplegic migraine type 2 (FHM2) have a mutated ATP1A2 gene (encoding Na +, K + -ATPase α2 subunit) and show prolonged migraine aura. Cortical spreading depression (CSD), which involves mass depolarization of neurons and astrocytes that propagates slowly through the gray matter, is profoundly related to aura. Methods: In two types of Atp1a2 -defective heterozygous mice, Atp1a2 tm1Kwk (C-KO) and Atp1a2 tm2Kwk (N-KO), the sensitivity and responsiveness to CSD were examined under urethane anesthesia. Results: In both cases, heterozygotes exhibited a low threshold for induction of CSD, faster propagation rate, slower recovery from DC deflection, and profound suppression of the electroencephalogram, compared to wild-type mice. A high dose of KCl elicited repeated CSDs for a longer period, with a tendency for a greater frequency of CSD occurrence in heterozygotes. The difference of every endpoint was slightly greater in N-KO than C-KO. Change of regional cerebral blood flow in response to CSD showed no significant difference. Conclusion: Heterozygotes of Atp1a2 -defective mice simulating FHM2 demonstrated high susceptibility to CSD rather than cortical vasoreactivity, and these effects may differ depending upon the knockout strategy for the gene disruption. These results suggest that patients with FHM2 may exhibit high susceptibility to CSD, resulting in migraine.